2012
DOI: 10.1016/j.cyto.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of Th17 associated cytokines in chronic hepatitis C virus infection

Abstract: The Th17-mediated immune response was investigated in patients chronically infected with hepatitis C virus (HCV) by determining the serum levels of the cytokines involved in the induction of the Th17 response (TGF-β and IL-6), the cytokines produced by Th17 cells (IL-17A, IL-17F and IL-22) and the cytokines whose production is stimulated by Th17 lymphocytes (IL-8 and GM-CSF). We investigated the relationships among the levels of these cytokines by assessing clinical findings, liver histology and viremia. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 32 publications
7
34
1
1
Order By: Relevance
“…Confirming several studies [36][37][38], we observed a remarkable higher frequency of Th17 cells in blood of CHC patients with respect to healthy individuals, and a slight increase in NAFLD/NASH subjects. Interestingly, NLCD was able to induce a consistent reduction of Th17-cell frequency in CHC patients, but not in our cohorts of NAFLD/NASH patients.…”
Section: Discussionsupporting
confidence: 73%
“…Confirming several studies [36][37][38], we observed a remarkable higher frequency of Th17 cells in blood of CHC patients with respect to healthy individuals, and a slight increase in NAFLD/NASH subjects. Interestingly, NLCD was able to induce a consistent reduction of Th17-cell frequency in CHC patients, but not in our cohorts of NAFLD/NASH patients.…”
Section: Discussionsupporting
confidence: 73%
“…[21][22][23][24] Cytokine ratios within the same axis may also be a marker of immune pathway activation, as has been reported for the IL-17F/IL-22 ratio in chronic hepatitis C infection 25 or for the IL-17/transforming growth factor-b ratio in schizophrenia. 26 A significant positive correlation has been demonstrated between the IL-17/IL-6 ratio and SLE disease activity as assessed by SLEDAI-2k, 27 which is consistent with data from the present study showing a positive correlation between the IL-17/ IL-23 ratio and disease activity.…”
Section: Discussionmentioning
confidence: 95%
“…Reverse transcription was performed using a TaqMan Õ Reverse Transcription Kit (Applied Biosystems, Foster City, CA, USA) in a total reaction volume of 100 ml with 2 mg of total RNA. Quantitative realtime reverse-transcription polymerase chain reaction (RT-PCR) was performed in a total reaction volume of 25 …”
Section: Quantitative Rt-pcr Analysis Of Il-23 and Il-17 Mrnamentioning
confidence: 99%
“…[12] Results also showed a highly significant decrease (P <0.01) in trimmed mean of IL-17 serum levels in HBV patients when compared to HCV patients group (Z = -4.321). In agreement, Sousa [15] found the mean of IL-17 serum level in HCV patients to be (96.8ng/L) while Du [16] found the mean of Il-17 in HBV patients to be (38.9 ng/L), which is lower than in HCV cases. The reason of this difference could be attributed to stimulation of Th17 cells by the HCV through expression of thymic stromal lymphopoietin (TSLP) which is essential factor in the differentiation and proliferation of Th17 cells.…”
Section: Levels Of Interleukin 17 (Ng/l) In Studied Groupsmentioning
confidence: 59%